2017
DOI: 10.1016/j.gpb.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Primate-Specific Long Non-Coding RNAs and MicroRNAs

Abstract: Non-coding RNAs (ncRNAs) are critical regulators of gene expression in essentially all life forms. Long ncRNAs (lncRNAs) and microRNAs (miRNAs) are two important RNA classes possessing regulatory functions. Up to date, many primate-specific ncRNAs have been identified and investigated. Their expression specificity to primate lineage suggests primate-specific roles. It is thus critical to elucidate the biological significance of primate or even human-specific ncRNAs, and to develop potential ncRNA-based therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 96 publications
(133 reference statements)
1
73
0
Order By: Relevance
“…It has been shown the binding of miRNAs to lncRNAs could decrease miRNA levels, which results in increasing in the expression of miRNA target genes (Awan, Shah, Rashid, & Shan, ; L. J. Li, Leng, Fan, Pan, & Ye, ). SphK2 has been proven to be a target of miR‐613 in PTC (Qiu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown the binding of miRNAs to lncRNAs could decrease miRNA levels, which results in increasing in the expression of miRNA target genes (Awan, Shah, Rashid, & Shan, ; L. J. Li, Leng, Fan, Pan, & Ye, ). SphK2 has been proven to be a target of miR‐613 in PTC (Qiu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Results demonstrated that inhibitory effects on cell proliferation, migration, and invasion induced by LINC00460 knockdown were partially reversed by inhibition of miR-613 in the meantime. These findings indicated that the oncogene LINC00460 promoted PTC progression by negatively regulating miR-613.It has been shown the binding of miRNAs to lncRNAs could decrease miRNA levels, which results in increasing in the expression of miRNA target genes(Awan, Shah, Rashid, & Shan, 2017;L. J. Li, Leng, Fan, Pan, & Ye, 2017).…”
mentioning
confidence: 84%
“…11 Long non-coding RNAs (lncRNA) are a novel class of ncRNAs and generally longer than 200 nucleotides. 12 Surging evidence has illuminated that lncRNAs are participated in the development of numerous cancers through epigenetic modification, transcriptional or post-transcriptional modulation and mRNA processing. 13 LncRNA LOXL1 antisense RNA 1 (LOXL1-AS1) located on human chromosome 15q24.1 is consisted of 10 781 nucleotides and five exons.…”
mentioning
confidence: 99%
“…The long noncoding RNAs (lncRNAs) are transcribed RNA molecules with a length more than 200 nucleotides. They lack open reading frames which have key regulatory effects in both transcription and post‐transcription . It is well known that lncRNAs play different roles in many important biological processes, including regulation of transcriptional and posttranscriptional process, epigenetic control, differentiation and development, cell cycle control, apoptosis, and metabolic processes .…”
Section: Introductionmentioning
confidence: 99%
“…They lack open reading frames which have key regulatory effects in both transcription and post-transcription. 13,14 It is well known that lncRNAs play different roles in many important biological processes, including regulation of transcriptional and posttranscriptional process, epigenetic control, differentiation and development, cell cycle control, apoptosis, and metabolic processes. 15 Regarding gene expression control, lncRNAs have been proposed, as recruiting epigenetic modifiers at a particular genomic locus.…”
mentioning
confidence: 99%